Adaptation of structures of steel laser hardening zones to friction conditions - A. V. Brover (Advanced Engineering Research)
Introduction. The structural state of the surface layers of engineering products manufactured through laser processing under various irradiation modes is considered. Structures with the highest possible stability with respect to external action under friction conditions, or with the possibility of optimal adjustment and additional hardening during operation by the formation of secondary structures, were implemented. Under the operating conditions, under the impact of mechanical and thermal pulses, an express rearrangement of one structure to another occurs, which is stable at a higher level of load-speed conditions. Thus, the phenomenon of structural-energy adaptability is realized. The resulting adapt-able structures most efficiently dissipate the energy introduced into the tribosystem, and minimize the wear of friction pairs.Materials and Methods. We studied samples of P6M5 steel using the following equipment:• Kvant-16 processing station with a power density of 100 MW/m2 for pulsed laser irradiation of samples;• Neophot-21 optical microscope for metal physical studies;• DRON-0.5 diffractometer for phase composition identification.Results. It is established that the material of the samples after laser treatment is able to efficiently dissipate the energy supplied during friction through its transformations at various structural levels. As a result, it becomes possible to control the surface strength and wear resistance of materials using the concept of structural adaptability of friction pairs, which extends their range of performance. Wear resistance of the irradiated steels is determined by both their initial hardness and the work-hardenability during friction. It is established that the thermal-strength loading of the steel sur-face irradiated layers during friction destabilizes austenite to the γ→α transformation, i.e., it contributes to its transformation into deformation martensite.Discussion and Conclusions. In relation to the specific loading conditions, it is required to regulate the amount and degree of stability of the residual austenite in laser-hardened steels and alloys, which provides the necessary operational properties.